Supply Chain and Demand of Online Products Business After COVID-19 Situation for Creative Economy Prachuapkhirikhun Province - Pinchumpholsang, Weerawan (Rajapark Journal, 2024)
This research aimed to study 1) the supply chain and demand of online product businesses after COVID-19 on the economy in Prachuapkhirikhun. 2) Factors affecting market competition that increase competitive potential 3) market competitive relations to increase the online supply chain's sales potential. A mixed approach was used in the research. The sixty businesses in the qualitative study were selected proportionately, particularly randomly from six categories: drinks, sweets, food, clothing from the area, seaside souvenirs, and chili sauce. Additionally, 600 consumer samples from the population were proportionally sampled for the demand side of the quantitative study. The data collection method involved an in-depth interview on the supply side and a questionnaire on the demand side of creative business groups in the province. Analysis of data by descriptive statistics and multiple regression analysis. The research results were found as follows: 1) The financial potential of the dessert business had the fastest payback period, and the present value of net profit compared to the investment budget approached the quickest payback. The demand-side research found that marketing factors had affected product consumption satisfaction. The products were popular in the market for their product image, services, and prices. Females under 18 with higher education levels and incomes ranging from 8,001 to 25,000 baht are satisfied with business group consumption. However, marketing development must expand to increase sales in the digital age, considering changing sales times. 3) The competitive business after developing additional marketing potential was higher than 10 percent, namely for dessert and clothing. Every business could expect an increase in sales of 10.95 percent. The impact of income factors and expenses from supply chain costs are factors that affect business operations.